Strategies Adopted by Esp Students to Perform Oral Presentations Through Videos - Sandy T., Soto (2017)
This work aims at identifying the strategies that generate major differentiation in use among students enrolled in Technical English I and Technical English II, before, during, and after the development of video-based oral presentations. Sixty-nine students took part in the study. They recorded one video per week for over ten weeks. Those students who had recorded at least seven videos were considered for the study. The participants completed a questionnaire that was composed of forty-six Likert Scale items indicating strategies that students could apply before (24 items), during (14 items), and after (8) the recording of the videos. In the questionnaire, students reported the frequency with which they used those strategies. The data was analyzed by conducting an analysis of variance. The results show that the strategies for the recording of videos with significant differentiation in the population under study are the following. Before: the elaboration of storyboards, detailed review of the content, content rehearsal, memorization, and pronunciation of words practice. During: utilization of examples to illustrate ideas, use of mother tongue, repetition strategies, circumlocution, and recording the presentation several times. After: Comparison of their performance in the videos with their pe